A modelling & simulation based engineering approach for socio-cyber-physical systems - Thuy Nguyen (2017 IEEE 14th International Conference on Networking, Sensing and Control (ICNSC), 2017)
Today, most large and complex systems such as aircrafts or power grids integrate physical and human aspects with computing and networking, and therefore constitute so-called socio-cyber-physical systems (SCPS). Their engineering, from prospective and conceptual studies (to determine the scope of the system) through design and construction to operation, maintenance and upgrades, necessitates the cooperation and coordination of many teams representing different disciplines and viewpoints. In addition, such systems are subject to many constraints such as tight budget and schedule; high dependability, safety and security; need to innovate; long lifetime; changing and uncertain environments. This paper presents a modelling and simulation (M&S) based engineering approach that can address the challenges of large and complex SCPS, and more generally, of systems of SCPS (SoS). Contrary to "classical" M&S approaches relying on deterministic behavioural models that can be developed only in the final stages of the design process, the proposed approach relies on constraints models that specify envelopes of required or assumed behaviours, and that can be applied at any phase of the system lifecycle. Also, in order to manage complexity and the variety of viewpoints, the approach supports models composition, whereby models from different teams or at different phases of the process can be aggregated (top-down or bottom-up) and verified for consistency.